Mechanical studies of ABS reinforced carbon black blends: article - Ahmad Khalid, Nur Mayang Tirana; Mohd Alauddin, Sakinah (2019)
The usage of ABS has shown its potential in synthetic engineering plastics however many studies suggested that modifications should be made to assure the improvement on the mechanical properties of ABS. As the highlight of this research, carbon black blends were reinforcing into ABS and the mechanical properties of ABS reinforced carbon black blends are studied as the flexural modulus and impact strength are determined. The preparation for ABS/CB was carried out by using a Haake Rheomixer OS at melting point of 210°C at 5 to 60 rpm. The flexural testing and impact testing are conducted according to standard methods ASTM D790 and ASTM D256 respectively.